Life and Death of Activated T Cells: How Are They Different from Naïve T Cells? - Zhan, Yifan; Carrington, Emma M.; Zhang, Yuxia; Heinzel, Susanne; Lew, Andrew M. (Frontiers in Immunology, 2017)
T cells are pivotal in immunity and immunopathology. After activation, T cells undergo a clonal expansion and differentiation followed by a contraction phase, once the pathogen has been cleared. Cell survival and cell death are critical for controlling of numbers of naïve T cells, effector and memory T cells. While naïve T cell survival has been studied for a long time, more effort has gone into understanding the survival and death of activated T cells. Despite this effort, there is still much to be learnt about T cell survival, as T cells transition from naïve to effector to memory. One key advance is the development of inhibitors that may allow the temporal study of survival mechanisms operating in these distinct cell states. Naïve T cells were highly reliant on BCL-2 and sensitive to BCL-2 inhibition. Activated T cells are remarkably different in their regulation of apoptosis by pro- and anti- apoptotic members of the BCL-2 family, rendering them differentially sensitive to antagonists blocking the function of one or more members of this family. Recent progress in understanding other programmed cell death mechanisms, especially necroptosis, suggests a unique role for alternative pathways in regulating death of activated T cells. Furthermore, we highlight a mechanism of epigenetic regulation of cell survival unique to activated T cells. Together, we present an update of our current understanding of the survival requirement of activated T cells.